2023
DOI: 10.1021/acs.iecr.3c01469
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Enhancement of Hydrophobic Compounds in Aqueous Solutions Using Biobased Solvents as Hydrotropes

Abstract: Improving the aqueous solubility of poorly soluble hydrophobic compounds is a topic of great interest to the pharmaceutical, chemical, and food industries. The poor solubility of these compounds in water poses a challenge in developing sustainable processes for their extraction, separation, and formulation. Therefore, in this study, the use as hydrotropes of biobased solvents such as γ-valerolactone (GVL), Cyrene, ethyl lactate, and alkanediols (1,2-propanediol, 1,5-pentanediol, and 1,6-hexanediol) to improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Ideally, solubility enhancement with hydrotrope concentration should attain a sigmoidal curve shape; however, here, all DES-based systems deviate from the sigmoidal shape perhaps because of the presence of specific interactions between ETA with DES. Similar findings have been reported in the literature earlier. The quantitative trend in water intake depends on the structure of the constituents of the DES. The initial maximum of w o observed for (Thy: DA) lies in the ETA concentration range between 0.9 and 1.5 M; for (Men: DA), it is between 0.8 and 1.6 M; for (Lin: DA), it is between 0.5 and 1.2 M; for (Cit: DA), it is between 0.5 and 1.1 M; and for (Ger: DA), it is between 0.7 and 1.8 M.…”
Section: Results and Discussionsupporting
confidence: 89%
“…Ideally, solubility enhancement with hydrotrope concentration should attain a sigmoidal curve shape; however, here, all DES-based systems deviate from the sigmoidal shape perhaps because of the presence of specific interactions between ETA with DES. Similar findings have been reported in the literature earlier. The quantitative trend in water intake depends on the structure of the constituents of the DES. The initial maximum of w o observed for (Thy: DA) lies in the ETA concentration range between 0.9 and 1.5 M; for (Men: DA), it is between 0.8 and 1.6 M; for (Lin: DA), it is between 0.5 and 1.2 M; for (Cit: DA), it is between 0.5 and 1.1 M; and for (Ger: DA), it is between 0.7 and 1.8 M.…”
Section: Results and Discussionsupporting
confidence: 89%
“…In this context, ionic liquids (ILs) can be a perfect choice, as this new generation of materials is known to possess tunable physicochemical properties, a wide liquidious range, and can solubilize a variety of solutes. Unfortunately, however, despite significant research efforts, it is still difficult to completely understand the mechanism and devise a general rule for protein stability in ILs. This is primarily due to certain odd effects that distinct proteins suffer in the presence of different ILs. , For instance, some ILs are reported to stabilize the proteins, whereas others show the opposite effect. , Zhang and co-workers have shown that increasing the concentration of ILs has an adverse effect on the BSA structure …”
Section: Introductionmentioning
confidence: 99%